Reciprocity in ethnobotanical research: case of a study carried out in the Mbe plain of Adamawa, Cameroon - Maxime, Lamy Lamy Georges; Phalone, Kenne Meli; Dalatou, Talba; Constantin, Amougou Alega; Adoum, dona; Laela, Zambou Zebaze; Rosette, Ndjib; Guidawa, Fawa; Germo, Nzweundji Justice; Néhémie, Donfagsiteli Tchinda; Gabriel, Agbor Agbor; Jean, Poom Bidou Vincent; et al. (Ethnobotany Research and Applications, 2020)
Background: The reciprocity in the exchanges between the local populations who hold the authentic traditional knowledge that they share with the conservation biologists was not sufficiently taken into account. For fairness and justice in these exchanges, the Nagoya Protocol on Access and Benefit-sharing was established. However, there is a lack of information on access and benefit sharing in unfunded ethnobotanical studies in Africa (MS and PhD research). Traditional knowledge on Detarium microcarpum Guill. & Perr. a multipurpose Fabaceae, unfortunately threatened with extinction, exists in Adamawa, Cameroon. Thus, in relation to a Master Research thesis without funding, a study was dedicated to this plant. Methods: Ethnobotanical methods have made it possible to test the following hypothesis: for an equal number of men and women, the points attributed according to gender to the categories of reciprocity experienced during an ethnobotanical study without funding are equal. Thirty available informed consent volunteers (15 men and 15 women) with knowledge on this plant participated in this study. Results: The majority socio-economic information was: [36-65] years old (66.67%), uneducated (for those with zero years of formal schooling) i.e. 53.34%, agriculture (source of income for men and women) i.e. 63.34%, Dii (66.67%) and Muslims (73%) respectively for age groups, level of education, main activity, ethno-linguistic group and religion. Overall, the "exchange of knowledge" was the reciprocity with more points (31.79%). The analysis of variance (ANOVA) revealed a non-significant difference (P ˃ 0.05) between the sexes. Thus, in the unfunded ethnobotanical study conducted in the study area, experienced reciprocity were not gender dependent. Conclusions: For this case study carried out in the Mbe plain (Adamawa, Cameroon), six categories of reciprocity were tested: Volunteer, material gift, co-author citation, Acknowledgement citation, report back and exchange of knowledge. These proposals for reciprocity may serve as a reference for future similar studies. Keywords: Nagoya Protocol, respondent, informed consent, reciprocity, Detarium microcarpum, Cameroon Résumé Contexte: La perte du savoir locale accélérée favorisera le protocole de Nagoya sur l’accès et le partage de ses avantages. Ainsi, lors des études financées, des réciprocités contribueront à encourager les populations à conserver durablement leurs savoirs. Cependant, un manque d’informations existe sur l’accès et le partage des avantages lors des études ethnobotaniques non financées en Afrique (Master recherche et Thèse de Doctorat/PhD). Un savoir traditionnel sur Detarium microcarpum Guill. & Perr., une Fabaceae multifonctionnelle malheureusement menacée de disparition existe dans l’Adamaoua, Cameroun. Ainsi, relativement à un mémoire de Master Recherche sans financement, une étude lui a été dédiée. Méthodes: Des méthodes ethnobotaniques ont permis de tester l’hypothèse suivante: pour un nombre d’hommes et femmes égal, les points attribués selon le sexe aux catégories de réciprocité expérimentées lors d’une étude ethnobotanique sans financement sont égaux. Trente volontaires (15 hommes et 15 femmes) de consentement éclairé, disponibles ayant un savoir sur la plante ont participé. Résultats: Les informations socio-économiques majoritaires étaient: [36-65] ans (66,67 %), sans instruction (pour ceux ayant zéro année d’école formelle) soit 53,34%, agriculture (source de revenus des hommes et femmes) soit 63,34 %, Dii (66,67 %) et musulmans (73%) respectivement pour tranches d’âge, niveau d’instruction, principale activité, groupe ethnolinguistique et religion. Globalement, l’« échange de savoirs » était la réciprocité ayant plus de points (31,79%). L’analyse de variance (ANOVA) a révélé une différence non significative (P ˃ 0,05) entre les sexes. Donc, lors de l’étude ethnobotanique sans financement réalisée dans la zone d’étude, les réciprocités expérimentées ne dépendaient pas du sexe. Conclusion: Pour cette étude réalisée dans la plaine de Mbé (Adamaoua, Cameroun), six catégories de réciprocité ont été expérimentées: Bénévolat, cadeau matériel, citation co-auteur, citation remerciement, compte rendu et échange de savoirs. Ces propositions de réciprocité pourront servir de référence aux études similaires ultérieures. Mots-clés: Protocole de Nagoya, enquêté, consentement éclairé, réciprocité, Detarium microcarpum, Cameroun